2013
DOI: 10.1111/vop.12069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prophylactic antiglaucoma and anti‐inflammatory medications in canine primary angle‐closure glaucoma: a multicenter retrospective study (2004–2012)

Abstract: None of the four antiglaucoma medications evaluated statistically delayed medical failure when compared to each other. Although significance was not achieved, our data suggest that adjunctive use of topical anti-inflammatory medications may be beneficial in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…There was no significant difference found between the 2 forms of prophylactic therapy; rather, they both seemed equally effective in delaying the onset of glaucoma in the fellow eye. 13 In a more recent study by Dees and colleagues, 14 4 different prophylactic therapies were evaluated in the fellow eye of dogs with primary narrow-angle glaucoma both with and without adjunctive anti-inflammatory therapy. Although mathematical differences in the median time until the onset of glaucoma existed, these values were not statically significant form each other.…”
Section: Prophylactic Treatment Of Primary Canine Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference found between the 2 forms of prophylactic therapy; rather, they both seemed equally effective in delaying the onset of glaucoma in the fellow eye. 13 In a more recent study by Dees and colleagues, 14 4 different prophylactic therapies were evaluated in the fellow eye of dogs with primary narrow-angle glaucoma both with and without adjunctive anti-inflammatory therapy. Although mathematical differences in the median time until the onset of glaucoma existed, these values were not statically significant form each other.…”
Section: Prophylactic Treatment Of Primary Canine Glaucomamentioning
confidence: 99%
“…From the data it seems that the choice of prophylactic antihypertensive agent may not be as important as the inclusion of a topical anti-inflammatory drop. 14 The authors typically recommend the use of dorzolamide (2%) every 12 hours and topical prednisolone acetate (1%) or neomycin/polymyxin/dexamethasone drops every 24 to 48 hours for the prophylactic treatment of confirmed or suspected idiopathic canine glaucoma. Immune-mediated mechanisms are commonly reported in medical literature and the association of an anti-inflammatory for the treatment/prevention of canine glaucoma is surely justified, especially considering the role that intraocular mononuclear cells may assume in the species.…”
Section: Prophylactic Treatment Of Primary Canine Glaucomamentioning
confidence: 99%
“…Although the mechanisms of glaucoma development are incompletely understood, GD is considered a cause of primary glaucoma in the dog, referred to here as GDAG 3 or PACG 3,10,15,[17][18][19][20] ; it has been referred to as GD-related glaucoma in one study. 4 GDAG/PACG is also known as primary open-angle closed-cleft glaucoma, 3,10,21 primary closed-angle glaucoma, or simply primary glaucoma.…”
Section: Glaucoma-induced Changes In the Canine Anterior Segmentmentioning
confidence: 99%
“…Though it has been reported in meetings that corticosteroids may have a negative effect on the hypotensive effect of latanoprost in normal dogs, contrary to our findings in the present study, Dees et al . reported improved clinical outcome in glaucomatous dogs when combining hypotensive and anti‐inflammatory drugs . Dogs with unilateral primary angle‐closure glaucoma whose contralateral, nonglaucomatous eyes were treated prophylactically with anti‐inflammatory drugs (prednisolone, dexamethasone or diclofenac) in conjunction with prophylactic hypotensive treatment (including latanoprost) had a delayed onset of glaucoma compared to eyes that were treated only with hypotensive drugs (324 days vs. 195 days, respectively) although the difference was not statistically significant …”
Section: Discussionmentioning
confidence: 99%
“…A morphologic study of canine globes with goniodysgenesis‐related primary glaucoma revealed significant histopathologic evidence of inflammation, suggesting that inflammation has an important role in the pathogenesis of the disease . Further supporting these histological findings, a recent clinical study reported improved outcome when topical anti‐inflammatory and antiglaucoma drugs were used concurrently in prophylactic treatment in canine primary angle‐closure glaucoma . As latanoprost is a PG analog that is frequently used to treat canine glaucoma, and as certain cases of glaucoma may require additional anti‐inflammatory treatment, we asked whether anti‐inflammatory drugs could potentially decrease the hypotensive effect of latanoprost.…”
Section: Introductionmentioning
confidence: 91%